Mujeres en la Cumbre - Ruiz, Aseneth Suarez (Spain : Suarez Ruiz, Aseneth, 2009)
“Women on the Summit” is a documentary that recounts moments in the lives of five women who are neighbors in “The summit”, a neighborhood on the edge of Bolivar city (a locality on the outskirts of Bogota, Colombia). The film explores the everyday lives of Luz Maria and her daughter Yadith, Berenice and her daughter Angelica, and Aunt Raquel, who formed a community association, exclusively for local women, to improve the quality of life in their neighborhood. This subsequently transformed their lives as well. Some footage shot by the women themselves is included in the film. The narration, told in their own words, is in fact a chorus of voices that relates how they have overcome adversity in their daily lives. Through common effort, the women on the summit have come to believe in themselves and are continuing to move forwards.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films